2000
DOI: 10.1128/jvi.74.19.8867-8875.2000
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions at the Putative Receptor-Binding Site of an Encephalitic Flavivirus Alter Virulence and Host Cell Tropism and Reveal a Role for Glycosaminoglycans in Entry

Abstract: The flavivirus receptor-binding domain has been putatively assigned to a hydrophilic region (FG loop) Virus attachment to the host cell is the first stage of the virus replication cycle. It requires the molecular interaction between the virion surface and a host cell receptor and is often the basis for viral species and tissue tropisms as well as virulence properties. The cellular receptors for some viruses have been defined and reveal diverse strategies for virus attachment, ranging from binding to specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 46 publications
6
124
0
Order By: Relevance
“…Interestingly, in the E protein, the tripeptide (TGP) of ROCV within domain III was found to be different from those observed in all other JEV members (RGX, where X is D, E or T). As the RGD motif is speculated to be involved in the virus adsorption to host cells for JEV and MVEV, two important JEV group flaviruses (Bhardwaj et al, 2001;Lee & Lobigs, 2000) and as it was also found in ALFV and USUV, further experimental studies for ROCV are needed to investigate the role of the TGP tripeptide in the mechanisms that involve the viruscell interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the E protein, the tripeptide (TGP) of ROCV within domain III was found to be different from those observed in all other JEV members (RGX, where X is D, E or T). As the RGD motif is speculated to be involved in the virus adsorption to host cells for JEV and MVEV, two important JEV group flaviruses (Bhardwaj et al, 2001;Lee & Lobigs, 2000) and as it was also found in ALFV and USUV, further experimental studies for ROCV are needed to investigate the role of the TGP tripeptide in the mechanisms that involve the viruscell interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the E protein, the tripeptide (TGP) of ROCV within domain III was found to be different from those observed in all other JEV members (RGX, where X is D, E or T). As the RGD motif is speculated to be involved in the virus adsorption to host cells for JEV and MVEV, two important JEV group flaviruses (Bhardwaj et al, 2001;Lee & Lobigs, 2000) and as it was also found in ALFV and USUV, further experimental studies for ROCV are needed to investigate the role of the TGP tripeptide in the mechanisms that involve the viruscell interaction.The functional roles of the 39-NCR of flaviviruses have been recently studied and the roles in the genomic cyclization between the 59-and 39-NCRs, viral replication and translation were elucidated. Moreover, the putative changes in the highly conserved regions related to important biological functions of the flaviviruses (survival and/or pathogenicity) were recognized (Bryant et al, 2005;Khromykh et al, 2001).…”
mentioning
confidence: 99%
“…Indeed, mice lacking caspase-3 displayed tissue, placenta, and amniotic fluid of newborns with microcephaly and in the stillborn infants of women infected by Zika during pregnancy [28]. The envelope protein of encephalitic arboviruses is the major determinant of neurotropism and neurovirulence, owing to its role in receptor binding and virus entry [177][178][179]. However, sequence analysis of virulent and attenuated strains of these viruses revealed that other regions of the viral genome, including the 3´ untranslated region and nonstructural proteins, also contribute to neurovirulence and viral tropism [180].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 99%
“…Flaviviruses, such as JEV, yellow fever virus, West Nile virus, Murray Valley encephalitis (MVE), and St. Louis encephalitis virus, have variable affinities for GAGs; this property contributes to viral attachment to host cells [8,12,[16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%